2016
DOI: 10.1111/ejn.13316
|View full text |Cite
|
Sign up to set email alerts
|

Parallel inputs from the mediodorsal thalamus to the prefrontal cortex in the rat

Abstract: There is a growing interest in determining the functional contribution of thalamic inputs to cortical functions. In the context of adaptive behaviours, identifying the precise role of the mediodorsal thalamus (MD) in particular remains difficult despite the large amount of experimental data available. A better understanding of the thalamocortical connectivity of this region may help to capture its functional role. To address this issue, this study focused exclusively on the specific connections from the MD to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
54
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 75 publications
(99 reference statements)
15
54
2
Order By: Relevance
“…As recently reported in the mosue 22 , this reflects the presence of two distinct and topographically organized MD-mPFC circuits. This topographic and reciprocal MD-PFC organization is consistent with anatomical findings in primates 19 and rats 20,21 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As recently reported in the mosue 22 , this reflects the presence of two distinct and topographically organized MD-mPFC circuits. This topographic and reciprocal MD-PFC organization is consistent with anatomical findings in primates 19 and rats 20,21 .…”
Section: Resultssupporting
confidence: 90%
“…Our pathway-specific experiments do not distinguish between dorsal and ventral mPFC (Supplementary Fig. 2), which reciprocally connect with lateral and medial MD in a largely segregated manner 21,22 . It is therefore possible that the distinct phase-specific behavioral impairments we observe may be attributable to activity in discrete MD-mPFC circuits, a possibility that will be important to resolve in future research.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Differences in the power of the fast oscillations between subregions may also reflect the extent and nature of afferent inputs to each subregion. For example, the lateral MD nucleus has extensive arborizations to both ACC and PrL, while the medial MD projects to PrL and IL (Vertes et al 2015; Kuramoto et al 2016; Alcaraz et al 2016), but we still know very little about inputs to DP.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly there is evidence for strong interregional interactions in vitro (van Aerde et al 2008), but further studies using inactivation of specific subregions would be required to reveal the extent, and direction, of interregional interactions within the mPFC in vivo. Alternatively, as outlined above, the dorsal to ventral differences may reflect different inputs to mPFC subregions (Vertes et al 2015; Alcaraz et al 2016). In addition, we have found that in the DP region the peak spindle, beta, and gamma power, relative to the onset of the Up-state, occurs much later and is more variable.…”
Section: Discussionmentioning
confidence: 99%